2005
DOI: 10.1159/000081778
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Blood-Aqueous Barrier Breakdown after Phacoemulsification in Fuchs’ Heterochromic Uveitis

Abstract: Purpose: To quantify the breakdown of the blood-aqueous barrier (BAB) following phacoemulsification with posterior chamber lens implantation in eyes with Fuchs’ heterochromic uveitis (FHU). Patients and Methods: In this retrospective study, 19 eyes of 19 patients with FHU (mean age 38 ± 14 years) and 35 eyes of 35 patients with senile cataracts (mean age 63 ± 9 years) underwent phacoemulsification with one-piece PMMA posterior chamber lens implantation. Aqueous flare was quantified using the laser flare-cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
14
0
4
Order By: Relevance
“…It is noteworthy that flare levels do not change with anti-inflammatory Review CME treatment and remain stable over months or years in this entity [7,37,38]. A relatively mild and stable breakdown of the blood-aqueous barrier has been reported in FU even after cataract surgery [33,36,39,40]. LFP studies have confirmed the clinical observations on the disease course and helped in explaining the benign nature of FU [41].…”
Section: Fuchs' Uveitismentioning
confidence: 96%
See 1 more Smart Citation
“…It is noteworthy that flare levels do not change with anti-inflammatory Review CME treatment and remain stable over months or years in this entity [7,37,38]. A relatively mild and stable breakdown of the blood-aqueous barrier has been reported in FU even after cataract surgery [33,36,39,40]. LFP studies have confirmed the clinical observations on the disease course and helped in explaining the benign nature of FU [41].…”
Section: Fuchs' Uveitismentioning
confidence: 96%
“…A relatively mild disruption of the blood-aqueous barrier has been shown in eyes with Fuchs' uveitis (FU), with mean flare values ranging from 6.4 to 12.1 ph/ms that were still significantly higher compared with fellow eyes or eyes of healthy controls [32][33][34][35][36][37]. It is noteworthy that flare levels do not change with anti-inflammatory Review CME treatment and remain stable over months or years in this entity [7,37,38].…”
Section: Fuchs' Uveitismentioning
confidence: 99%
“…The accuracy and reproducibility of the method have been shown in several studies. [12][13][14][15][16][17][18][19][20][21][22][23] Using LFCM, we recently showed breakdown of the BAB and presence of anterior chamber cells in Chinese patients with Fuchs syndrome. 7 The present study confirmed our previous observation in another group of Chinese patients with Fuchs syndrome using the same technique.…”
Section: Eyementioning
confidence: 99%
“…However, breakdown of the blood-aqueous barrier is relatively mild in FUS, with mean flare values ranging from 6.4 to 12.1 ph/ms [46,[54][55][56]. In eyes with some but not all clinical features of this entity, for example in eyes with diffuse keratic precipitates, mild iris atrophy, vitreous cells and debris but without heterochromia or cataract, low flare readings help the differential diagnosis from other forms of chronic granulomatous uveitis.…”
Section: Fuchs Uveitis Syndrome (Fus)mentioning
confidence: 99%